The French Republic under Cavaignac, 1848 - De Luna, Frederick A. (Frederick Adolph), 1928- (Book collections on Project MUSE., 2015)
General Louis Eugene Cavaignac has been a symbol of reactionary violence ever since he crushed the insurgent workers of Paris in the "bloody June Days" of 1848. Professor de Luna presents a fresh interpretation of the General, as well as a detailed examination of the turbulent year of European revolution, until Cavaignac was defeated by Louis Bonaparte in the December presidential elections. Many historians have dismissed the Cavaignac period as one of bleak reaction, but Professor de Luna shows that the General was a fervent democratic republican, and that the moderate republicans under Cavaignac offered their own program of political, economic, and educational reform.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.